Desain Model Pembelajaran Berbasis Masalah Untuk Meningkatkan Kemampuan Berpikir Kritis Matematika Siswa SMP - Isman M. Nur; Hujairah Hi. Muhammad; Diah Prawitha Sari (Peneliti.net, 2023)
The aims of this research are a) to improve students' mathematical critical thinking skills after applying problem-based learning models and conventional learning models; b) How are students' attitudes towards problem-based learning; c) To obtain an overview of student activities during the problem-based learning process. This study used the pretest-posttest design experimental method. The research subjects were class VIII students of SMP Negeri 1 Rancakalong, with two classes as the sample. The research instrument used was a description test of mathematical critical thinking skills, an attitude scale and an observation sheet. The results showed that: (1) the students' mathematical critical thinking skills who received problem-based learning were better than students who received conventional learning; (2) most students show a positive attitude towards mathematics and problem-based learning ; 3) during the learning process students are very active, feel happy, help each other give opinions and solve problems or assignments given in the problem-based learning model.